Radiative heat energy exploration on Casson-type nanoliquid induced by a convectively heated porous plate in conjunction with thermophoresis and Brownian movements. Issue 1 (31st December 2022) - Shamshuddin, MD.; Ghaffari, A.; Usman
Abstract : The interest of this study is to establish a mathematical model and rheological aspects of chemically reacting Casson-type nanofluid flow considering ethylene glycol-based nanoparticles with thermophoretic diffusion and Brownian motion. The basic flow equations are transmuted into non-dimensional form, these dimensionless leading equations are determined to the most excellent potential systematic using some influential similarity transformations with the employment of the Chebyshev Spectral Collocation method. The outcomes for flow rate, temperature, concentration and engineering quantities distribution are shown in terms of graphical presentation. Findings revealed that larger values of Casson fluid parameter lead to suppress velocity as well as fluid temperature. The nanofluid temperature reduces for Brownian motion parameter and enchances for thermophoresis parameter. An increase in Lewis number means a decrease in mass diffusivity resulted in to suppression in fluid concentration. The model results confirmation is tabulated, and the data assessment of the present study with formerly communicated is found excellently accurate.